The Influence of Transformational Leadership Style and Permissive Attitude on The Quality of Financial Reports of Bos Funds in Educational Institutions - Fitria, Pipit (Pascasarjana STIE Amkop Makassar, 2025)
This quantitative study examines the impact of transformational leadership style and permissive attitude on the quality of financial reports of School Operational Assistance (BOS) funds in private high schools and vocational vocational schools in Cirebon. The study involved 157 BOS treasurers with a final sample of 32 respondents selected using purposive sampling. The findings, analyzed through multiple linear regression reveal that transformational leadership style positively influences the quality of financial reports, whereas a permissive attitude has no significant effect. These results suggest that the transformational leadership approach influences the quality of financial reports within educational institutions at high/vocational schools in Cirebon. additionally, the study provides insights for educational institutions to establish leadership principles that promote financial accountability. However, this study is limited by the low participation rate in completing the distributed surveys. Keywords: Transformational Leadership Style, Permissive Attitude, Financial Report Quality